Study Of Supervision, Leadership, and Compensation on Employee Work Discipline in Medan Denai Sub-District - Juniarti Juniarti; Pradini, Putri (Universitas Kristen Indonesia Toraja, 2024)
This study is to determine the feasibility of supervision, leadership, and compensation in influencing employee work discipline in Medan Denai Sub-district. This study was conducted with descriptive qualitative with literature study method through literature studies sourced from previous research journals. The results show that effective supervision contributes significantly to improving employee work discipline, with higher levels of compliance. In addition, supportive and participative leadership styles were also found to have a strong positive influence on work discipline, encouraging employee motivation and engagement. Fair and competitive compensation was also shown to play an important role, where employees who were satisfied with the rewards they received tended to show better levels of discipline. Supervision, leadership, and compensation are important factors in improving employee discipline. There is a need for companies to implement better supervision strategies, promote supportive leadership, and ensure competitive compensation to maximize employee discipline and productivity. Recommendations for future research include a deeper exploration of the specific mechanisms linking supervision and leadership to work discipline.